2019
DOI: 10.1177/1079063218821108
|View full text |Cite
|
Sign up to set email alerts
|

Criminogenic Needs as Intervening Factors in the Relation Between Insecure Attachments and Youth Sexual Violence

Abstract: There is a strong theoretical and research base demonstrating the link between attachment styles and adolescent sexual offending. However, this relationship may be best explained by deficit-based mediational pathways including criminogenic needs such as emotional or affect regulation and callousness. Grady, Levenson, and Bolder propose a framework that details criminogenic needs as intermediary variables in the attachment–sexual offending relationship. Using data on adolescents adjudicated of sexual and nonsex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…For example, among a large sample of male YSH, 13% had a history of sexual abuse (compared with 5% of delinquent youth), 20% had a history of physical abuse (15% of delinquent youth), and 11% had a history of physical neglect (6% of delinquent youth; Levenson et al, 2017): All differences were statistically significant. Furthermore, cumulative or multiple forms of trauma may be higher among YSH when compared with delinquent youth (Levenson et al, 2017; J. Yoder et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, among a large sample of male YSH, 13% had a history of sexual abuse (compared with 5% of delinquent youth), 20% had a history of physical abuse (15% of delinquent youth), and 11% had a history of physical neglect (6% of delinquent youth; Levenson et al, 2017): All differences were statistically significant. Furthermore, cumulative or multiple forms of trauma may be higher among YSH when compared with delinquent youth (Levenson et al, 2017; J. Yoder et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Yoder & Precht, 2019). In another study, researchers found that executive functioning mediated the relationship between sexual abuse victimization and the commission of sexual harm (J. Yoder et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, the current study included predictor variables, including prior sexual victimization, 4 which would fall into the category of ACEs. Prior literature has found that ACEs in individuals with a prior sexually based offense differ from those without this history (Yoder, Dillard, and Leibowitz (2018); Yoder et al, 2019), including in samples of Florida youth (Levenson et al, 2017). This relationship is not present in the current analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical examinations have found support for this perspective. Youth with prior sexual offense involvement and with exposure to harsher and indifferent maternal caregiving were found to have higher child abuse experiences in comparison with youth with nonsexual offense history (Yoder, Grady, & Dillard, 2018; see also Yoder, Grady, Brown, & Dillard, 2019).…”
Section: Theoretical and Evidentiary Backgroundmentioning
confidence: 98%
“…In recent years, the SOST field has looked more closely at treatment in terms of a growing appreciation for the prevalence and impact of early childhood adversity and trauma among youth and men who sexually abuse (Grady, Levenson, & Bolder, 2017;Yoder, Grady, Brown, & Dillard, 2019). In a widely cited study using the Adverse Childhood Experience scale, Levenson, Willis and Prescott (2014b) found that men who sexually abuse had experienced three times the rate of child sexual abuse, twice the rate of physical abuse, 13 times the rate of verbal abuse, and four times the rate of emotional neglect and broken homes.…”
Section: Appreciation Of the Impact Of Trauma And Attachment Deficitsmentioning
confidence: 99%